Implementasi Rocchio’s Classification dalam Mengkategorikan Renungan Harian Kristen - Elisabeth Adelia Widjojo; Antonius Rachmat C; R. Gunawan Santosa (Ultimatics : Jurnal Teknik Informatika, 2014)
Nowadays, many Christian institutions are using digital media to save spiritual pictures, musics or videos, even daily devotional articles which is usually printed monthly. Since many daily devotionals are published in the Internet, it will be difficult to find a daily devotional articles with a spesific topic/category. To make it easier, in this research we use Rocchio’s classification, which use TF-IDF weighting for classification and centroid calculation in every category to classify daily devotional articles. Every testing article will be matched with the centroid using cosine similariy. As a result, the system accuracy is 73,33% using 20% of feature selection. The highest precision goes to Wisdom category which score is 1 for precision by using 100% feature selection. While the highest recall goes to Motivaton category which score is 1 by using 100% feature selection.. Index Terms—classification, categorization, daily devotional article, Rocchio’s classification, centroid, similarity